Analisis Leukosit Urine Dipstik dan Kultur Bakteri Pada Pasien Diabetes Mellitus di Kota Ternate - Nurdin, Erpi; Zuchrullah, Mukhtasyam; Nasarudin, Sandi (Poltekkes Kemenkes Jambi, 2024)
Background: Diabetes mellitus sufferers with poor diabetes control will generally develop urinary tract infections. Methods: This is a descriptive study, namely to obtain a dipstick urine leukocyte picture and bacterial culture in diabetes mellitus patients in Ternate City. Results: The research results showed that there were 21 female respondents (66%) and 11 male respondents (34%), and the frequency of age in the late elderly category was more dominant, namely 13 people (41%). Based on the length of time they have suffered from diabetes mellitus, with >10 years, there are 20 people (63%). The frequency of blood glucose increasing based on Point of Care Testing (POCT) examination was 23 people (72%). The urine culture results of diabetes mellitus patients showed that the average urine bacteria number was 6,3.103 CFU/mL with the interpretation of possible urinary tract infection (UTI), namely 11 people (34%), and 6,0.101 CFU/mL with the interpretation of no UTI, being 21 people (66%). Conclusion: Based on the research results, it was concluded that 3 respondents (9%) had positive leukocyte values despite the possibility of an UTI, and 8 respondents (25%) had negative leukocyte values despite the possibility of an UTI. There were 11 respondents (34%) with increased blood glucose accompanied by the possibility of UTI, and 3 respondents (9%) with increased blood glucose accompanied by positive leukocyte values.